Extracorporeal cardiopulmonary resuscitation for out-of-hospital cardiac arrest: first results and outcomes of a newly established ECPR program in a large population area. (April 2022) - Djordjevic, Ilija; Gaisendrees, Christopher; Adler, Christoph; Eghbalzadeh, Kaveh; Braumann, Simon; Ivanov, Borko; Merkle, Julia; Deppe, Antje-Christin; Kuhn, Elmar; Stangl, Robert; Lechleuthner, Alex; Miller, Christian; et al.
Objectives: Out-of-hospital cardiac arrest (OHCA) is associated with excessively high mortality rates. Recent studies suggest benefits from extracorporeal cardiopulmonary resuscitation (ECPR) performed in selected patients. We sought to present the first results from our interdisciplinary ECPR program with a particular focus on early outcomes and potential risk factors associated with in-hospital mortality. Methods: Between January 2016 and December 2019, 44 patients who underwent ECPR selected according to our institutional ECPR protocol were retrospectively analyzed regarding pre-hospital, in-hospital, and early outcome parameters. Patients were divided into survivors (S) and non-survivors (NS). Statistical analysis of risk factors regarding in-hospital mortality of the patient cohort analyzed was performed. Results: The mean age of the population was 53 ± 12 years, with most patients being male ( n  = 40). The leading cause of cardiac arrest (CA) was myocardial infarction ( n  = 24, 55%). The median hospital stay was 1 (1;13) day. Twenty-three percent of patients ( n  = 10) were discharged from hospital including eight patients (18%) with CPC 1–2. Survivors showed a trend toward shorter pre-hospital CPR duration (60 (59;60) min (S) vs 60 (55;90) min (NS), p = 0.07). Conclusion: Establishing ECPR programs in large population areas offers the option to improve survival rates for OHCA patients. Stringent compliance of institutional criteria (mainly age, witnessed arrest, and time of pre-hospital resuscitation) and providing ECPR to strictly selected patients seems to be a vital factor for such programs' success. Pre-clinical settings and therapeutic measures must be adjusted in this regard to improve outcomes for this highly demanding patient cohort.